No significant increase in long‐term CH4 emissions on North Slope of Alaska despite significant increase in air temperature. Issue 12 (22nd June 2016) - Sweeney, Colm; Dlugokencky, Edward; Miller, Charles E.; Wofsy, Steven; Karion, Anna; Dinardo, Steve; Chang, Rachel Y.‐W.; Miller, John B.; Bruhwiler, Lori; Crotwell, Andrew M.; Newberger, Tim; McKain, Kathryn; et al.
Abstract: Continuous measurements of atmospheric methane (CH4 ) mole fractions measured by NOAA's Global Greenhouse Gas Reference Network in Barrow, AK (BRW), show strong enhancements above background values when winds come from the land sector from July to December from 1986 to 2015, indicating that emissions from arctic tundra continue through autumn and into early winter. Twenty‐nine years of measurements show little change in seasonal mean land sector CH4 enhancements, despite an increase in annual mean temperatures of 1.2 ± 0.8°C/decade (2 σ ). The record does reveal small increases in CH4 enhancements in November and December after 2010 due to increased late‐season emissions. The lack of significant long‐term trends suggests that more complex biogeochemical processes are counteracting the observed short‐term (monthly) temperature sensitivity of 5.0 ± 3.6 ppb CH4 /°C. Our results suggest that even the observed short‐term temperature sensitivity from the Arctic will have little impact on the global atmospheric CH4 budget in the long term if future trajectories evolve with the same temperature sensitivity. Key Points: Twenty‐nine years of CH4 observations at Barrow, AK, suggest emissions stagnant despite warming Seasonal CH4 emissions at Barrow continue late into December Projected enhancements in Arctic CH4 emissions will have small global impact